Optimalisasi Produksi dan Pengenalan Sistem ABC Sederhana dalam Usaha Peningkatan Perekonomian Pengrajin Purun Desa Bengkel - Munawarah; Yuni Lestari br Sitepu; Tetty Yuliaty (Universitas Medan Area, 2023)
Purun crafts are still widely carried out by community groups of craftsmen in Bengkel Village. Its durability makes it a very durable product so it has high value. The service activity aims to provide partners with knowledge in optimizing purun woven production by using press machine technology which can minimize the duration and costs incurred during purun woven production as well as providing dyes which can increase the creativity of craftsmen in producing variety of attractive and marketable products. This condition encourages the implementing team to provide simple socialization and training on how to calculate simple unit costs using the ABC system. Partners are equipped with understanding of the use of social media and e-commerce to market these woven products in various directions. Sales can increase and encourage partner economic growth. This activity shows maximum results as can be seen from Partner's enthusiasm in using machines as well as understanding good financial calculations and management, as well as marketing methods that are in line with the progress of the times. The results of the difference test show a sig value of 0.001, meaning there is a difference between before and after the activity was carried out in Bengkel Village.